Remoçada: a espetacularidade da torcida organizada nos jogos do Clube do Remo em Belém do Pará - LOBATO, Eugênia Cristina dos Santos (2019)
This research presents a study about the spectacle of the Torcida Organizada Remoçada in the soccer matches by Clube do Remo in Belém Pará, in attempt to understand this phenomenon of this sport in Pará. As the theoretical-methodological support for the present research, we have adopted the Ethnocenology, starting from Spectacle Rites as a subset of PCHEOS (Organized Human Spectacle Wonts and Behaviours) proposed by Armindo Bião (2009) to this Ethnoscience of Arts and Kinds of Spectacle, besides studies regarding the Sociology of Orgy by Michel Maffesoli (2000) which discuss the emotional communities nowadays and the theories of Rudolf Laban in order to analise the bodies of the soccer rooters in their movements and gestures within this spectacular practice.